2022
DOI: 10.3390/jcm11113087
|View full text |Cite
|
Sign up to set email alerts
|

Association between Masseter Muscle Area and Thickness and Outcome after Carotid Endarterectomy: A Retrospective Cohort Study

Abstract: Low muscle mass is associated with adverse outcomes after surgery. This study examined whether facial muscles, such as the masseter muscle, could be used as a proxy for generalized low muscle mass and could be associated with deviant outcomes after carotid endarterectomy (CEA). As a part of the Vascular Ageing study, patients with an available preoperative CT-scan, who underwent an elective CEA between December 2009 and May 2018, were included. Bilateral masseter muscle area and thickness were measured on preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…In the current study, total POCUS muscle thickness had the strongest correlation (r = 0.73) with CT-derived SMI. It is possible that, as a recently published study found a significant association between lower masseter muscle thickness as a derivate of low generalized muscle mass with deviant surgical outcomes after vascular surgery, adding POCUS masseter muscle measurements to the total POCUS muscle thickness may improve the correlation with CT-derived SMI [37]. On the other hand, given the limited time available in clinical practice, one could also consider measuring only m. biceps brachii thickness (r = 0.66) because measuring both the arm and the leg muscles is more time-consuming.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, total POCUS muscle thickness had the strongest correlation (r = 0.73) with CT-derived SMI. It is possible that, as a recently published study found a significant association between lower masseter muscle thickness as a derivate of low generalized muscle mass with deviant surgical outcomes after vascular surgery, adding POCUS masseter muscle measurements to the total POCUS muscle thickness may improve the correlation with CT-derived SMI [37]. On the other hand, given the limited time available in clinical practice, one could also consider measuring only m. biceps brachii thickness (r = 0.66) because measuring both the arm and the leg muscles is more time-consuming.…”
Section: Discussionmentioning
confidence: 99%